Accelerated DOM Scripting with Ajax, APIs, and Libraries - Snook, Jonathan (Apress, 2012)
I’d like to take the time to acknowledge the many people who helped and inspired me to write this book. Thanks to the entire Apress team, especially Chris Mills and Richard Dal Porto, for being so incredibly patient. I’m also honored to have such great and knowledgeable coauthors: Dan Webb, Aaron Gustafson, and Stuart Langridge. Thanks much to Cameron Adams for doing the tech review. I’ll be sure to buy you all a drink the next time we meet in person.